2009
DOI: 10.1121/1.3021306
|View full text |Cite
|
Sign up to set email alerts
|

Effects of obstruent consonants on fundamental frequency at vowel onset in English

Abstract: When a vowel follows an obstruent, the fundamental frequency in the first few tens of milliseconds of the vowel is known to be influenced by the voicing characteristics of the consonant. This influence was re-examined in the study reported here. Stops, fricatives, and the nasal /m/ were paired with the vowels /i,Ä/ to form CVm syllables. Target syllables were embedded in carrier sentences, and intonation was varied to produce each syllable in either a high, low, or neutral pitch environment. In a high-pitch en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 32 publications
(14 reference statements)
6
95
1
3
Order By: Relevance
“…Tais resultados concordam com a análise acústica realizada, pela comparação da produção do traço de sonoridade para as plosivas /b/, /d/ e /g/ entre um grupo de crianças disfônicas, com maior ocorrência de dessonorização, e um grupo de crianças sem alterações de fala 2 . Esse tipo de estudo, demonstra que, por meio de aná-lises fonético-acústicas e interpretação dos espectrogramas, relações entre os aspectos físicos e linguísticos podem ser identificadas 6,11,13 , auxiliando na compreensão da correlação entre o processo articulatório e o evento acústico resultante, e da relação entre os processos de produção e percepção da fala 10,12 . Este tipo de análise permite relacionar os distúrbios da fala, linguagem, voz e audição com os processos fisiológicos envolvidos em sua ocorrência 16 , bem como demonstrar que a criança tenha conhecimentos fonológicos não visualizáveis em sua produção motora [17][18][19] .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Tais resultados concordam com a análise acústica realizada, pela comparação da produção do traço de sonoridade para as plosivas /b/, /d/ e /g/ entre um grupo de crianças disfônicas, com maior ocorrência de dessonorização, e um grupo de crianças sem alterações de fala 2 . Esse tipo de estudo, demonstra que, por meio de aná-lises fonético-acústicas e interpretação dos espectrogramas, relações entre os aspectos físicos e linguísticos podem ser identificadas 6,11,13 , auxiliando na compreensão da correlação entre o processo articulatório e o evento acústico resultante, e da relação entre os processos de produção e percepção da fala 10,12 . Este tipo de análise permite relacionar os distúrbios da fala, linguagem, voz e audição com os processos fisiológicos envolvidos em sua ocorrência 16 , bem como demonstrar que a criança tenha conhecimentos fonológicos não visualizáveis em sua produção motora [17][18][19] .…”
Section: Discussionunclassified
“…A estratégia de dessonorização representa a dificuldade na coordenação dos eventos gló-ticos e supraglóticos 6,7 . Um atraso no início da sonorização faz as oclusivas soarem como surdas, demonstrando um comprometimento na organização têmporo-espacial dos movimentos dos Órgãos Fonoarticulatórios (OFA) 8 , podendo ser afetado por treinamento e tipo de tarefa 9 , bem como por aspectos contextuais verbais 10,11 e não-verbais 12 e até dialetais 13 . Outro aspecto que se deve investigar na aná-lise da dessonorização é a percepção e sua relação com a produção.…”
Section: Introductionunclassified
“…It was also present in early peaks in German but absent in Russian. At first, the effect was suggestive of a microprosodic influence of surrounding voiceless consonants (e.g., Hanson, 2009). However, being (a) not very close to a voiceless consonant and (b) of a considerable magnitude (1 st), the non-local upscaling may be too prominent for a purely microprosodically driven effect.…”
Section: Cross-linguistic Comparisons Of Pitch-segment Interactionsmentioning
confidence: 99%
“…In case of intervening voiceless consonants (like in target words Schiffer, Кашивкин), the velocity of the glide was reconstructed by interpolation between the preceding H and the following L target. Local microprosodic fluctuations in pitch tracks due to immediately adjacent obstruents were excluded from the annotations of turning points (e.g., Hanson, 2009). …”
Section: Data Preparationmentioning
confidence: 99%
“…A closer investigation of these segmental effects in this and other studies revealed that the effect of the voiced/voiceless dichotomy occurred primarily in the early part of a vowel, near its onset (Hombert et al, 1979;Ohde, 1984; see also Hanson, 2009, for a review). These f0 variations can be explained as arising from a carryover effect of glottal stiffening or slackening gestures involved in the production of the preceding consonants that cause the vocal folds to vibrate faster in vowels following a voiceless obstruent than in vowels following a voiced obstruent (Halle and Stevens, 1971;Löfqvist et al, 1989).…”
Section: The Effects Of Obstruent Consonant Voicing On Vowel F0mentioning
confidence: 99%